Pemanfaatan Media Konkret "Make a Match" sebagai Upaya Meningkatkan Antusiasme Belajar Murid SDN Rowobelang - Muhammad Fahrun Nada; Puja Wahyu Ningrum; Mutiara Lutfi Ghumaisa; Ega Putra Sabana; Affan Rafi Saputra; Rina Nuraeni (Jurnal Pendidikan UNIGA, 2026)
This study aims to examine the role of concrete media based on the Make a Match game in increasing the interest and enthusiasm of third-grade students at SDN Rowobelang in learning about Indonesian Cultural Diversity. The background of this study is rooted in the low enthusiasm for learning of students, which is evident from passive behavior, lack of participation, and minimal focus during learning. Using a qualitative approach with a descriptive design, this study collected data through observation, interviews, and documentation. All data were analyzed using the interactive model of Miles and Huberman, which includes the stages of data reduction, data presentation, and drawing conclusions. The results showed that the application of the concrete media Make a Match was able to significantly increase student enthusiasm and activeness. Students were seen to be more active in discussions, showed increased focus, and built positive interactions during the learning process. In terms of learning outcomes, most students were able to master the material very well through completing the Student Worksheet (LKM), and all students were able to answer oral evaluation questions correctly. These findings confirm that the Make a Match media is effective in creating an active, collaborative learning atmosphere and has a positive impact on conceptual understanding. Keywords: Make a Match, Concrete Media, Enthusiasm for Learning, Pancasila Education, Elementary School